2020
DOI: 10.1111/bju.15019
|View full text |Cite
|
Sign up to set email alerts
|

The N6‐methyladenosine (m6A) erasers alkylation repair homologue 5 (ALKBH5) and fat mass and obesity‐associated protein (FTO) are prognostic biomarkers in patients with clear cell renal carcinoma

Abstract: Objectives To comprehensively investigate the role of the N6‐methyladenosine (m6A) erasers ALKBH5 and FTO in clear cell renal cell carcinoma (ccRCC), other RCC subtypes, and oncocytoma with respect to prognostic value and biomarker potential. Patients and Methods The collection of tissue samples was performed within the framework of the Biobank at the Centre for Integrated Oncology Cologne‐Bonn. The gene expressions of alkylation repair homologue 5 (ALKBH5) and fat mass and obesity‐associated protein (FTO) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 28 publications
1
54
1
Order By: Relevance
“…As for other cancers, ALKBH5 was significantly downregulated in clear cell renal cell carcinoma (ccRCC) compared to normal tissue [45]. It was also affirmed that ALKBH5 took a great part in contributing to osteosarcoma tumorigenesis [40].…”
Section: Alkbh5 In Other Cancersmentioning
confidence: 89%
See 1 more Smart Citation
“…As for other cancers, ALKBH5 was significantly downregulated in clear cell renal cell carcinoma (ccRCC) compared to normal tissue [45]. It was also affirmed that ALKBH5 took a great part in contributing to osteosarcoma tumorigenesis [40].…”
Section: Alkbh5 In Other Cancersmentioning
confidence: 89%
“…Chu et al [32] and Feng et al [33] respectively identified the crystal structure of zebrafish ALKBH5 (fALKBH5) and human ALKBH5, which promoted the understanding of the substrate recognition specificity of ALKBH5 and offered a foundation for the development of inhibitors selective for NAOX. In addition, Xu et al [34] affirmed Clear cell renal cell carcinoma Downregulated --- [45] Osteosarcoma --Proliferation and tumor growth PVT1 [40] Oral squamous cell carcinoma --Chemoresistance FOXM1, NANOG [46] the m6A binding pocket of ALKBH5 and the key residues related with m6A recognition through mutagenesis and isothermal titration calorimetry binding experiments. Furthermore, m6A served as a 'conformational marker' , which induced different conformational outcomes in RNAs depending on sequence context and critically impacted its interactions with ALKBH5 [35].…”
Section: The Structure Of Alkbh5mentioning
confidence: 99%
“…Methylation levels in miRNAs are also potential diagnostic biomarkers for early-stage gastrointestinal cancers [166]. The m 6 A erasers ALKBH5 and FTO are also shown to be prognostic biomarkers in patients with clear cell renal carcinoma [167]. From Table 1, some RNA modification enzymes are also tightly related to the grades and may predict the prognosis of GBM.…”
Section: Potential Diagnostic Implications Of Rna Modifications In Gbmmentioning
confidence: 99%
“…Strick et al conducted qRT-PCR to detect the gene expressions of ALKBH5 and FTO were studied in 166 ccRCC and 106 normal renal tissues. They found that the expression level of ALKBH5 and FTO were obviously decreased in ccRCC tissues (Strick et al, 2020). Declined mRNA levels of ALKBH5 and FTO were related to a shortened overall and cancer-specific survival following nephrectomy.…”
Section: Rna M 6 a As Biomarker In Urological Tumorsmentioning
confidence: 98%